2012
DOI: 10.1088/1367-2630/14/10/103018
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional crossover transition in a system of weakly coupled superconducting nanowires

Abstract: Owing to recent observations of superconductivity in quasi-onedimensional (1D) systems, Josephson arrays composed of aligned and weakly coupled 1D superconducting nanowires have attracted renewed interest for modeling the experimental data. Carrying out Monte Carlo simulations, we go beyond the traditional mean field results to show that the competition between 1D fluctuations and the transverse Josephson coupling between the nanowires can lead to a 1D-3D crossover transition at a temperature T c below the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…24,26,29,[34][35][36][37][38][39][40] Na 2−δ Mo 6 Se 6 is not an inhomogeneous or granular superconductor in the traditional sense, where phase coherence is determined by the ratio of E J to E C for individual grains. 31,32 Instead, it is a crystalline superconductor whose normal state is a localized metal, due to the combination of Na vacancy disorder and intense 1D anisotropy. Signatures of localization are clearly visible in the normal-state resistance R NS , which diverges as T → 0 and displays a large negative magnetoresistance ( Fig.…”
Section: Mechanisms For Reentrancementioning
confidence: 99%
See 1 more Smart Citation
“…24,26,29,[34][35][36][37][38][39][40] Na 2−δ Mo 6 Se 6 is not an inhomogeneous or granular superconductor in the traditional sense, where phase coherence is determined by the ratio of E J to E C for individual grains. 31,32 Instead, it is a crystalline superconductor whose normal state is a localized metal, due to the combination of Na vacancy disorder and intense 1D anisotropy. Signatures of localization are clearly visible in the normal-state resistance R NS , which diverges as T → 0 and displays a large negative magnetoresistance ( Fig.…”
Section: Mechanisms For Reentrancementioning
confidence: 99%
“…Although Berezinskii-Kosterlitz-Thouless (BKT) transitions are generally considered to be a property of 2D materials, evidence for BKT-type behavior has been reported in experimental and numerical studies of q1D superconductors. 11,12,30,31 In Fig. S4(a), we sketch the spatial variation of the phase of the superconducting order parameter on each (Mo 6 Se 6 ) ∞ filament in a crosssectional "slice" perpendicular to the c (high-symmetry) axis.…”
Section: E Similarities To the 2d Bkt Transitionmentioning
confidence: 99%
“…This phase ordering transition triggers a dimensional crossover in the array from a 1D fluctuating superconducting state with finite resistance at high temperatures to a zero-resistance 3D bulk phase-coherent superconducting state in the low temperature regime. It has been shown that this transition falls into the same universality class as the famous Berezinski-Kosterlitz-Thouless (BKT) transition [22,23,24] in 2D superconducting systems [6], where a vortex-unbinding transition occurs through vortex excitations in the phases of the order parameters in groups of adjacent nanowires [3,4]. The Josephson phase current, which establishes the BKT-type transverse coupling, is very weak when the tunneling barrier is thick or the coherence length is short.…”
Section: Introductionmentioning
confidence: 95%
“…Quasi-1D superconductors represent intriguing materials that allow investigating quantum confinement effects, strong phase fluctuations, and critical phenomena, based on the fact that arrays of dense superconducting atomic chains or nanowires represent intrinsic Josephson junction arrays with unique critical phase transition behavior [1,2,3,4,5,6,7]. Of particular interest is the observation that under certain conditions the upper critical fields (Hc2) can be strongly enhanced with Hc2 values reaching up to a factor 200 of the value of the corresponding materials in their bulk form, and significant critical temperature (Tc) enhancements compared to the bulk state [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been shown that if one takes into account the dielectric screening effect of the nanotube array (on the electron-electron interaction), a superconducting ground state can indeed be realized in (5,0) carbon nanotubes [23][24][25]. Furthermore, theoretical Monte Carlo simulations on the Ginzburg-Landau model have shown that with the appearance of the superconducting condensate, even a very weak Josephson coupling between the aligned nanotubes can lead to a 1D to 3D (three-dimensional) crossover transition at a temperature below that where the superconducting condensate first appears [8,26].…”
Section: Introductionmentioning
confidence: 99%